2005
DOI: 10.1111/j.1365-2427.2004.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal adaptation of Arctic charr: experimental studies of growth in eleven charr populations from Sweden, Norway and Britain

Abstract: 1. Experimental growth data for Arctic charr (Salvelinus alpinus L.), all fed on excess rations, from 11 European watercourses between 54 and 70°N were analysed and fitted to a new general growth model for fish. The model was validated by comparing its predictions with the growth rate of charr in the wild. 2. Growth performance varied among populations, mainly because of variation in the maximum growth potential, whereas the thermal response curves were similar. The estimated lower and upper temperatures for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 47 publications
6
112
1
Order By: Relevance
“…Salmonids may thus have significant somatic growth at temperatures around 08C given nutrient-rich food, but such growth during winter can hardly explain the extent of energy depletion of the juveniles in the Stjørdalselva. Thermal adaptation has been compared among populations from a broad geographical area of different salmonids species, but there appears to be no significant intraspecific differences in thermal adaptation (Larsson et al, 2005). Energy conservation must therefore predominantly occur through behavioural change during the long-winter period in northern areas.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonids may thus have significant somatic growth at temperatures around 08C given nutrient-rich food, but such growth during winter can hardly explain the extent of energy depletion of the juveniles in the Stjørdalselva. Thermal adaptation has been compared among populations from a broad geographical area of different salmonids species, but there appears to be no significant intraspecific differences in thermal adaptation (Larsson et al, 2005). Energy conservation must therefore predominantly occur through behavioural change during the long-winter period in northern areas.…”
Section: Discussionmentioning
confidence: 99%
“…Fish that died during the experiment (19 out of 480) were replaced by similarly sized fish to maintain densities at 10 fish per tank, but the replacement fish were not included in the results. The setup of the growth performance experiments followed a well-documented and standardized protocol (Jonsson et al 2001, Finstad et al 2004, Larsson et al 2005, Forseth et al 2009). Mean mass (± SD) of the fish at start of the first growth experiment run was 6.2 ± 1.2, 9.0 ± 1.4, and 12.1 ± 2.2 g for natural, mixed and heated incubation temperatures, respectively, and 9.4 ± 2.4, 11.6 ± 2.5, and 14.7 ± 3.1 g for the second.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, recent experimental studies have not supported either of the first 2 hypotheses , Jonsson et al 2001, Larsson et al 2005, but leave the third possibility open. Circumstantial support for the third hypothesis was also given by a 25 yr long monitoring of the production of the anadromus salmonid Atlantic salmon Salmo salar L. in the River Imsa, Norway.…”
Section: Introductionmentioning
confidence: 97%
“…Arctic charr are found at higher latitudes than any other freshwater fish species and are therefore the species most likely to exhibit specific adaptations for surviving under conditions where winters are long and productivity is low. Laboratory studies of charr have found them capable of growing at very low temperatures (*2-5°C : Larsson et al 2005) while field and laboratory studies have shown that they feed throughout long periods of ice-cover (Klemetsen et al 2003;Svenning and Klemetsen 2007;Amundsen and Knudsen 2009) and can exhibit over-winter growth (Siikavuopio et al 2010). Size classes that have grown large enough to switch their diet from zooplankton to benthic invertebrates may feed better over winter since winter abundance of benthic invertebrates can be much greater than zooplankton abundance (Byström et al 2006;Hölker 2006).…”
Section: Specialization Survival Strategiesmentioning
confidence: 99%